“Diasporic Identity: A Transnational Consciousness”- in Rai’s There is a Carnival Today - Bhattarai, Punya Prasad (Adhyayan Journal, 2025)
The novel, Aja Ramita Chha by Indra Bahadur Rai translated as There is a Carnival Today in English by Thapa has been viewed applying concept of hybridity and diaspora of postcolonial theory as methodological tools propounded by Homi K Bhabha to analyze cultural identity of diaspora. Cultural identity of diaspora is hybridized because of affiliation and connectedness to both home land and host land. Identity of old diaspora connected to nation is replaced by new diaspora associated with trans -nation and globalization. The researcher has focused to answer the questions such as, how is the cultural identity of diaspora hybridized? What are the experiences that diasporas feel while living in in-between position? The researcher has used theory of diaspora to show the cultural affiliation with home land, and theory of transnationalism to explain mobility of the characters crossing the border. The concept of hybridity under diaspora has been applied to analyze the cultural aspect of the characters living in- between positions in the host land. The finding of the research is that diasporas living in the host land live through dual identity, double consciousness, conflicted mentality, divided self and hybrid identity because of their contentedness and affiliation to both land of origin and land of destination.